Bioguided isolation of cytotoxic triterpenoids from the stem of luvunga scandens - Al-Zikri, Putri Nurhidayah; Bakhtiar, M. Taher; Darnis, Deny Susanti; Rezali, Mohd Fazlin; Read, Roger W; Sohrab, Md. Hossain; Hasan, Choudhury Mahmood; Ahmad, Farediah (2015)

(untitled)
Luvunga scandens species belongs to the family of Rutaceae. This plant usually inhabit tropical and moist environment and known as ‘Mengkurat Jakun’ among locals. A bioactivity-guided isolation and chemical investigation of the stem of Luvunga scandens resulted in the isolation and characterization of triterpenoids, 3-oxotirucalla-7,24-dien-21-oic-acid (1), and flindissol (2). The structures of the compound were determined on the basis of spectroscopic analyses including 2D NMR. The inhibitory effects of 1–2 on the proliferation on human breast adenocarcinoma cell line (MCF-7) have been evaluated by MTT assay and their effects on cell cycle and apoptosis investigated by flow cytometry with the morphological observation under Scanning Electron Microscope (SEM). Compounds 1 and 2 showed potent cytotoxicity against MCF-7 cell line with IC50 values of 27.5 µM and 13.8 µM respectively. Flow cytometry investigations for 1–2 demonstrated that both compounds exert their anti-proliferative effect on MCF-7 cells through inhibiting cell cycle and inducing apoptosis. This result suggested that both compounds might be useful for anticancer agents.